ANDROID-BASED EMPLOYEE ATTENDANCE SYSTEM WITH USING THE LOCATED BASE SERVICE METHOD AT THE AIR PERIUKAN SUB-DISTRICT OFFICE - Putra, Rio Marenda Eka; Siswanto, Siswanto (Institut Bakti Nusantara, 2024)
In the current era of globalization, technological progress is very rapid, especially in the field of Technology. Where technological advances enter into all social, economic and educational fields. The development of computerized system needs The waterfall method is one of the SDLC models that is often used in the development of information systems or software.Black Box testing is a software testing method that tests the functionality of the application as opposed to the internal structure or work, this testing process tests to measure all attribute usability by application usersThe current attendance system requires a new system update. Because doing this will have a very good impact on the company in terms of efficiency, effectiveness and speed. This requires a design design before this system is made. Design an online attendance system using the LBS (Location Based Serviced) distance limiting method based on the Android application owned by each employee. This requires a local or internet network that is determined by the distance limit with the LBS whose coordinate points have been set. The system development method used is CASE (Computer-Aided-Software Engineering) using the concept of Unified Modeling Language (UML), while the diagrams used are Use Case Diagram, Activity Diagram and Class Diagram